1990
DOI: 10.1099/00221287-136-12-2421
|View full text |Cite
|
Sign up to set email alerts
|

Wall mannoproteins in cells from colonial phenotypic variants of Candida albicans

Abstract: Candida albicans ATCC 26555 switched at high frequency (10-l to between several phenotypes identified by colony morphology on a defined mineral amino-acid-containing agar medium supplemented with arginine and zinc (LAZ medium). When cells taken from colonies exhibiting distinct morphologies were plated directly onto LAZ agar, spontaneous conversion to all the variant phenotypes occurred at combined frequencies of 2-1 x 10-l to xHowever, when cells taken from the different colonial phenotypes were plated direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…C. albicans hyphal growth has been associated with both wrinkled colony morphology and biofilm formation on plastic surfaces (5, 37). We found that wrinkled colonies, formed upon growth on medium with GlcNAc at 37°C, exhibited some biofilm-associated characteristics, including cells in hyphal, pseudohyphal, and yeast morphologies that remained associated with one another even upon suspension in liquid (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…C. albicans hyphal growth has been associated with both wrinkled colony morphology and biofilm formation on plastic surfaces (5, 37). We found that wrinkled colonies, formed upon growth on medium with GlcNAc at 37°C, exhibited some biofilm-associated characteristics, including cells in hyphal, pseudohyphal, and yeast morphologies that remained associated with one another even upon suspension in liquid (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To map ␤-Man epitopes for the different CWMP families, we slightly modified the protocols generally used (10,48) to sequentially release CWMPs. ConA, a lectin specific for terminal ␣-D-mannosyl and ␣-D-glucosyl residues and widely used to detect CWMPs (1,26,39), served as a systematic control in this study. As one of the aims of this study was to compare the well-defined PPM to other CWMPs, it was important to release noncovalently bound proteins, like PPM, without detergents, even at a low concentration, to avoid any contamination with covalently bound mannoproteins.…”
Section: Resultsmentioning
confidence: 99%
“…The wrinkled structures of rugose colonies and pellicles have strikingly similar appearances in phylogenetically disparate organisms. Wrinkle-forming organisms that have become models for the study of biofilm morphogenesis include representatives from the genera Bacillus [1014], Candida [15,16], Escherichia [17,18], Pseudomonas [1921], Rhodospirillum [22], Saccharomyces [2325], Salmonella [26], Serratia [27], Vibrio [28,29] and members of the phylum Actinobacteria [30,31] (Figure 1). The extent of wrinkling varies widely between isolates, even within the same species, and is condition-dependent.…”
Section: Microbial Multicellularitymentioning
confidence: 99%